Improving Rural Economic Empowerment through Herbal Product Development: A Study of Sanggrahan Women Farmer Group - Widayati, Rina Sri; Khasanah, Aulia Uswatun; Suratman, Suratman; Amalina, Nur; Fanani, Galih Pramuja Inngam (LPPM Universitas Duta Bangsa Surakarta, 2025)
Rural communities often face challenges in utilizing local resources for economic empowerment. The Sanggrahan Women Farmer Group (KWT) in Sukoharjo has potential in cultivating family medicinal plants (TOGA), yet knowledge and skills in processing, packaging, financial management, and marketing remain limited. This study employed a participatory approach involving training, mentoring, and hands-on practice. The program included product innovation (jaselor, golor tea, moringa-based snacks), packaging design, financial literacy, and digital marketing. Pre-test and post-test assessments were conducted, supported by observation and documentation, with descriptive statistics and paired t-tests applied to measure changes. Findings revealed significant improvement in participants’ knowledge and skills. The proportion of members in the “good” knowledge category increased from 10% before training to 72% after training, while production skills improved from 12% to 73%. In addition, KWT successfully promoted products through social media and the village MSME Expo, gaining wider market exposure. Several products also obtained P-IRT certification, enhancing legitimacy and distribution potential. The results demonstrate that integrated empowerment—combining training, digital marketing, and certification—effectively strengthens women’s economic capacity and market readiness. This model is replicable in other rural settings and provides valuable insights for policymakers and development practitioners to foster sustainable, women-led economic empowerment.